DAMPAK EKONOMI MANDALIKA SEBAGAI DESTINASI WISATA INTERNASIONAL DAN TANTANGAN KEBUTUHAN SDM TERAMPIL - Made Arya Astina; Ketut Tri Budi Artani (Journal of Innovation Research and Knowledge, 2024)
The Province of West Nusa Tenggara (NTB) is one of Indonesia's top tourist destinations with great potential in the international tourism sector. The development of the Mandalika Special Economic Zone (Kawasan Ekonomi Khusus/KEK) as a priority tourist destination, supported by infrastructure projects such as the MotoGP Circuit, is expected to have a positive impact on the local economy. This research aims to analyze the extent of Mandalika's development impact on the local economy and to identify strategies for enhancing the skills of the local human resources (HR) in supporting economic growth. Using a descriptive qualitative approach, data were collected through interviews and observations with tourism business actors, academics, and local government representatives. The findings indicate that the Mandalika has both direct and indirect positive effects on the local economy, primarily through job creation and increased community income during international events. However, there is still a need to develop skilled human resources to improve the competitiveness and sustainability of tourism in the region. The proposed strategy includes continuous training involving academics, tourism entrepreneurs, associations, and local governments.